Fuel Production from Para-Rubber Dung by Pyrolysis - Taylitthy, Outhan; Leuangtakoun, Somsavath; Lathdavong, Lemthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to produce fuel from rubber using the pyrolysis method by studying three temperature levels (300, 350, and 400°C) and 20 kg of scrap rubber was used as a sample in the reactor. Using a slow pyrolysis process to evaluate their effects on the yield and properties of the fuel. Twenty kilograms of scrap rubber were processed in a stationary reactor. The reactor heating technique is to heat the hot steam box at 100°C with a fuel oil burner and control the temperature of the control unit at 30°C. The reactor operation takes 3 hours. The results showed that pyrolysis temperatures of 300°C, 350°C, and 400°C produced maximum fuel yields of 65wt%, 72wt%, and 61wt% by weight, respectively. From the analysis of fuel properties, it was found that the fuel obtained by pyrolysis at 350°C had the highest heating value of 39.1MJ/kg, high density and low viscosity, flash point-fire point at the temperature 25°C, and a minimum ash content of 0.5wt%. While the fuel obtained by pyrolysis at 400°C has a heating value of 36.8MJ/kg, low density, high viscosity and a maximum ash content of 1.3wt%. Therefore, for the pyrolysis of para-rubber dung, a temperature of 350°C is considered an appropriate temperature and can produce a relatively high amount of fuel.